2017
DOI: 10.1139/cgj-2016-0284
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the progressive collapse mechanism of excavations retained by cantilever piles

Abstract: An increasing number of catastrophic progressive collapses of deep excavations have occurred throughout the world. However, the research on progressive collapse mechanisms is limited. In this paper, two categories of model tests were conducted to investigate the mechanism of partial collapse (sudden failures of certain retaining piles) and progressive collapse. The model test results show that partial collapse can cause a sudden increase in the bending moments of adjacent piles via an arching effect. The load-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…e maximum bending moment value of the supporting piles in the core area of influence increases the most, indicating that the load is mainly transferred to this area. It can be further concluded that the loading effect caused by the construction of cutting supporting piles is the most significant in this area [37][38][39].…”
Section: Load Transfer Trends Of Supporting Piles After Cuttingmentioning
confidence: 92%
“…e maximum bending moment value of the supporting piles in the core area of influence increases the most, indicating that the load is mainly transferred to this area. It can be further concluded that the loading effect caused by the construction of cutting supporting piles is the most significant in this area [37][38][39].…”
Section: Load Transfer Trends Of Supporting Piles After Cuttingmentioning
confidence: 92%
“…The ratio of the pile wall bending moment when the reinforcement in the pile reaches the ultimate tensile strength to the design bending moment is the safety coefficient, K d . 37,38 If I . K d , the pile will be damaged; conversely, the pile will keep working if I \ K d .…”
Section: Deformation and The Internal Force Of The Pile Wallmentioning
confidence: 99%
“…As a result, the full potential of the steel supports is not realized [11], and the DC joint becomes a critical vulnerability in the steel support system, compromising the overall bearing capacity. The inadequate performance of these joints can lead to catastrophic failures, as evidenced by several foundation pit accidents [12][13][14].…”
Section: Introductionmentioning
confidence: 99%